Letter from Dr. Walter E. Massey to Dr. Henry McBay - Massey, Walter E. (1976)
Walter E. Massey (1938-) congratulates Henry McBay (1914-1995) for receiving the "Outstanding Teacher Award in Chemistry." Massey reminisces about his time as a student of McBay in 1954 and expresses his gratitude for McBay's teaching methods. Dr. Walter Massey was the first African American professor of physics at Brown University. From 1975-1979, he served as a Professor of Physics and College Dean at Brown.
Keywords: McBay, Henry C.; Massey, Walter E.; Scientists, Black; Chemistry teachers; Chemistry--Study and teaching (Higher)